2018
DOI: 10.1007/s00426-018-1059-7
|View full text |Cite
|
Sign up to set email alerts
|

Training and transfer effects of extensive task-switching training in students

Abstract: The capacity to switch between tasks is a central component of executive functioning. Previous studies assessing effects of task-switch training have revealed mixed results, both in terms of processes that may be improved and the extent of beneficial effects on non-trained tasks. These studies primarily used few training sessions, which may have limited training and transfer effects. Here, 31 students were trained for 21 days on a cued switching task. Both the trained group and an active control group (n = 29)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
3
15
1
1
Order By: Relevance
“…In this respect, studies on the trainability of cognitive flexibility already showed promising results (e.g. Grönholm-Nyman et al 2017;Zhao et al 2018). Further, current treatments for chronic pain such as mindfulnessbased interventions that aim at increasing EF and/or cognitive flexibility (Gallant 2016;Moynihan et al 2013;Ortner et al 2007) offer interesting new angles for future research on the relationship between EF and pain.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, studies on the trainability of cognitive flexibility already showed promising results (e.g. Grönholm-Nyman et al 2017;Zhao et al 2018). Further, current treatments for chronic pain such as mindfulnessbased interventions that aim at increasing EF and/or cognitive flexibility (Gallant 2016;Moynihan et al 2013;Ortner et al 2007) offer interesting new angles for future research on the relationship between EF and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The EF tasks are briefly described below; for further details see Zhao, Chen, and Maes (2018) and Zhao, Wang, and Maes (2018). In addition to these tasks, the participants also performed an IQ test but the corresponding data were not used because of the use of different tests for the age groups, complicating a direct comparison.…”
Section: Ef Tasksmentioning
confidence: 99%
“…For instance, von Bastian and Oberauer (2013) reported no evidence for far-transfer effects on reasoning, inhibition, and working memory after cue-based task-switching training in adults. Zhao et al (2018) discovered no far-transfer effects on untrained EF tasks and general IQ after extensive task-switching training in adults, while shortlived transfer effects on working memory were found for young children. On the contrary, Karbach and Kray (2009) studied children aged from seven to nine years, asking them to perform two simple decision tasks (A and B) and switch between them at a specific signal.…”
Section: Cognitive Training and Efmentioning
confidence: 87%